1981
DOI: 10.1055/s-2007-1019356
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine and Triiodothyronine Kinetics and Extrathyroidal Peripheral Conversion Rate of Thyroxine to Triiodothyronine in Healthy Elderly Humans

Abstract: The influence of age on the kinetics of thyroxine (T4) and triiodothyronine (T3), and on peripheral conversion of T4 to T3, has been studied, comparing a group of euthyroid, healthy, elderly individuals to a group of young individuals. A monocompartment model was adopted for the kinetics of T4, while a bicompartment model was used for T3. No significant difference (p greater than 0.05) could be found in any of the kinetic parameters of T4 between the elderly and young groups. However, the following significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
3
2
Order By: Relevance
“…In contrast to T 4 levels, serum free T 3 concentrations showed a significant decline with age in the present study, corresponding to the observations by Burrows et al (1975) and Rubenstein, Butler and Werner (1973). This observed fall in serum T 3 in old age has been suggested by Hansen, Skousted and Siersbaek-Nielsen (1975) to be caused by a decrease in T 3 production, whereas Mirales- Garcia et al (1981) suggested that an increased daily turnover of T 3 lowered serum T 3 .…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast to T 4 levels, serum free T 3 concentrations showed a significant decline with age in the present study, corresponding to the observations by Burrows et al (1975) and Rubenstein, Butler and Werner (1973). This observed fall in serum T 3 in old age has been suggested by Hansen, Skousted and Siersbaek-Nielsen (1975) to be caused by a decrease in T 3 production, whereas Mirales- Garcia et al (1981) suggested that an increased daily turnover of T 3 lowered serum T 3 .…”
Section: Discussioncontrasting
confidence: 60%
“…T4 metabolism has been shown in some studies to be reduced in the elderly (17), though this may be related to the increased frequencies of nonthyroidal illnesses and medication intake in this age group. T4 to T3 conversion appears to be normal in healthy elderly individuals (18)(19)(20), though some reduction has been reported (21). While some have recommended reduction in T4 replacement dosage in the elderly (22), the present findings would suggest the opposite.…”
Section: Aging Effect On T4 Absorptioncontrasting
confidence: 69%
“…Of these, five were above the age of 65 years (elderly group), the remainder were between the ages of 18 and 26 years (young group). Each subject received through an antecubital vein approximately 50 juCi of 125 I-T 3 (Amersham Radiochemical Center, England), which specific activity was 200-400 uCi/4.3-13.6 ug, following a previously described protocol (Miralles-Garcia, Garcia-Iglesias, De Pablo, Lanao and Castro 1981). Simultaneously, also by intravenous vein, 100 uCi of sterile 51 Cr-EDTA (Amersham Radiochemical Center, England) (specific activity 1-2 mCi/mg) was administered, for the simultaneous study of renal glomerular filtration, according to the bicompartmental model (Brien, O 'Hagan and Muldowney 1969).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work {Miralles- Garcia, Garcia-Iglesias, De Pablo, Lanao and Castro 1981), we have investigated the influence of age on the kinetics of both thyroid hormones, and the level of peripheral conversion of T 4 to T 3 in the elderly. We found no significant difference in the behavior of T 4 in these subjects.…”
Section: Introductionmentioning
confidence: 99%